2023
DOI: 10.3390/cancers15205014
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogenic Potential of Bisphenol A in the Liver Based on Transcriptomic Studies

Marta Wiszpolska,
Ewa Lepiarczyk,
Mateusz A. Maździarz
et al.

Abstract: Bisphenol A (BPA) is an environmental toxin widely used in the production of polycarbonate plastics. A correlation exists between BPA tissue contamination and the occurrence of pathological conditions, including cancer. First-passage detoxification of high BPA amounts in the liver promotes hepatotoxicity and morphological alterations of this organ, but there is a lack of knowledge about the molecular mechanisms underlying these phenomena. This prompted us to investigate changes in the liver transcriptomics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Therefore in our previous study, we have investigated changes in the liver transcriptomics of mice exposed to BPA in drinking water. Data from this study suggested that BPA has a significant impact on gene expression in this organ, and may alter pathways linked to the pathogenesis of severe metabolic liver disorders and malignant tumors, in particular hepatocellular carcinoma (Wiszpolska et al, 2023). About 1% of BPA does not break down and accumulates in tissues.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore in our previous study, we have investigated changes in the liver transcriptomics of mice exposed to BPA in drinking water. Data from this study suggested that BPA has a significant impact on gene expression in this organ, and may alter pathways linked to the pathogenesis of severe metabolic liver disorders and malignant tumors, in particular hepatocellular carcinoma (Wiszpolska et al, 2023). About 1% of BPA does not break down and accumulates in tissues.…”
Section: Introductionmentioning
confidence: 80%
“…The experiment was carried out on twelve, 3-month-old female mice (Mus musculus, C57BL6/J/CMDB strain) with an average body weight of 30 g. The same animals were used in our previous study to investigate changes in the liver transcriptomics of mice exposed to BPA in drinking water (Wiszpolska et al, 2023). Mice were kept in the animal house (at the Faculty of Veterinary Medicine, University of Warmia and Mazury in Olsztyn, Poland) under constant temperature 22 °C ± 20 °C, humidity 55% ± 10% and 12:12 h light-dark cycle.…”
Section: Laboratory Animalsmentioning
confidence: 99%
“…Potential role of BPA in inducing carcinogenicity cannot be underestimated as this endocrine disruptor is linked to causing hepatic tumours in adult mice 42 . BPA‐exposed liver transcriptome analysis points towards its association with malignant tumours 43 . Downregulation of genes like P53, BAX and P21 is reported in breast cancer cell line and liver of animal models 44 .…”
Section: Bisphenols Endocrine Disruption and Carcinogenicitymentioning
confidence: 99%
“…42 BPA-exposed liver transcriptome analysis points towards its association with malignant tumours. 43 Downregulation of genes like P53, BAX and P21 is reported in breast cancer cell line and liver of animal models. 44 Similarly, ovarian cancer was found to be aggravated in both in vitro and in vivo in experimental models through oestrogen receptor alpha (Erα) signalling.…”
Section: B Is Phenol S Endocrine Dis Rup Tion and C Arcinog Enicit Ymentioning
confidence: 99%